Efficacy of combined non-invasive brain stimulation and robot-assisted gait training on lower extremity recovery post-stroke: a systematic review and meta-analysis of randomized controlled trials - Wang, Jiaoyun; Zhang, Huihuang; Ma, Jiani; Gu, Lei; Li, Xiang (Frontiers in Neurology, 2025)
BackgroundLower extremity dysfunction post-stroke significantly impedes patient independence and quality of life. Non-invasive brain stimulation (NIBS) and robot-assisted gait training (RAGT) have individually shown promising outcomes in gait recovery. However, the synergistic efficacy of non-invasive brain stimulation combined with robot-assisted gait training remains uncertain. This systematic review and meta-analysis aim to evaluate the combined therapy’s effectiveness on gait improvement and related motor functions in stroke patients.MethodsFollowing PRISMA guidelines, a comprehensive search was conducted to identify randomized controlled trials (RCTs) published up to September 2024. The primary outcome was assessed using the 6-min walk test (6MWT), with secondary outcomes examining assessed using the Functional Ambulation Category (FAC); the Motion Index (MI) to analyze exercise intensity; the Modified Ashworth Scale (MAS) to assess spasticity; and spatiotemporal gait parameters (SPG).ResultsSix randomized controlled trials involving 191 stroke patients were included. Meta-analysis revealed that combined non-invasive brain stimulation and robot-assisted gait training significantly improved the 6-min walk test scores (mean difference [MD] = 21.81, 95% CI = 0.03–43.59), though effects on strength, activity participation, spasticity, and coordination were non-significant.ConclusionNon-invasive brain stimulation combined with robot-assisted gait training shows potential in enhancing gait function but provides limited additional benefits for other motor functions. This combined approach may serve as an effective rehabilitation strategy for post-stroke gait recovery, warranting further large-scale studies to refine intervention protocols.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42021283890.